PEMBELAJARAN AGAMA DAN LINGKUNGAN DALAM KULTUR SEKOLAH ALAM: POTENSI MEMBUMIKAN KESADARAN LINGKUNGAN SEJAK DINI DI SEKOLAH - Abdulloh Hadziq (Universitas Islam Negeri (UIN) Mataram, 2016)
This study attempts to identify how the concept of the integration between religion and nature environment of learning process in PAUD Sekolah Alam Ungaran (SAUNG) Semarang is, and its impact for realizing student behavior in protecting nature eternity. Applying field research as a qualitative study, researcher used observation, interviews, and documentation as the method of collecting data. Data analysis of the study is descriptive by using data from manager, teacher, student and parents. Meanwhile, this study also used phenomenology as the approach for finding the essence of school culture. This paper Founds that PAUD SAUNG Semarang integrated its learning process through sunnah kauniyah in nature and social life combined with Islamic precepts or the integration between dalil kauniyah and dalil naqliyah. On the other side, PAUD SAUNG Semarang used integrative method using Contextual Teaching and Learning (CTL) as the learning model. It also supported by unique classroom design, the curriculum (combination of Islam precepts and nature environment) and outdoor activity in learning process. So, it can improve student’s awareness to love their nature